Infrared thermography in marine applications - Pašagić, Vladimir; Mužević, Marijan; Kelenc, Dubravko (2008)
Infrared (IR) thermography has become a powerful tool for basic and applied scientifi c research and for the application in various fi elds such as industry, environment, military and maritime affairs, etc. As a „predictive“ maintenance tool, IR thermography has the ability to identify problems before they occur. It is especially helpful for trouble shooting potential electrical overloads, worn or bad circuit breakers and buses. IR thermography can also be used to detect bad bearings, shafts, worn pulleys or any application where heat detection would be benefi cial. This paper has the intention to familiarize researchers, engineers and sea business staff with possibilities of applying IR thermography in the fi eld of maritime affairs. Therefore, basic principles of IR thermography are presented and examples of the tool application are given
Bibliografija: 12 jed
Sažetak
Keywords: Termografija -- Primjena -- Brodogradnja